Investigation of extended blinks and interblink intervals in subjects with and without dry eye - Rodriguez, John D (Dove Medical Press, 2013)
BACKGROUND: The purpose of this study was to investigate the occurrence and duration of extended blinks ≥ 70 msec and their associated interblink intervals in normal subjects and in subjects with mild to moderate dry eye. METHODS: This single-center, prospective, double-blind study included 11 subjects with dry eye and eight subjects with normal eyes. Extended blinks were defined as lid closure in at least two successive video frames (≥70 msec). Digital video imaging of each subject’s eyes was recorded while the subject viewed a 10-minute documentary. The subjects did not know that blink was the outcome being measured. Following capture, the videos were manually analyzed in a masked fashion for the occurrence of extended blinks. The length of the interblink interval (ie, time between blinks) before and after these extended blinks (the interblink interval ratio) was calculated, as well as differences in lid contact times. RESULTS: The dry eye group had a median extended blink duration which was 2.53 times longer than that of the normal group. For subjects with dry eye, interblink intervals post-extended blink were significantly longer than interblink intervals pre-extended blink (P < 0.001). Interblink intervals did not lengthen significantly in normal subjects. In both groups, the duration of the extended blink was significantly (P = 0.001) and positively correlated with interblink interval ratio (post-extended to pre-extended blink interblink interval), such that for each doubling of extended blink duration, the interblink interval ratio increased by 10%. Blinks longer than one second in duration occurred almost exclusively in subjects with dry eye. CONCLUSION: This study reports three central findings: blink duration tended to be longer in subjects with dry eye; a lengthening of the interblink interval after an extended blink occurred in subjects with dry eye but not in those without dry eye; and a longer blink duration was associated with a significantly increased interblink interval ratio in all subjects.